Abed Al-Jabiri's Epistemology of Intelligence: A Case Study of Interfaith Marriage in Indonesia - Agus Sutono; Fuad Noorzeha (IAIN Pekalongan, 2022)
Interfaith marriage/mixed marriage is currently an unresolved social polemic. It means that the marital status of different religions is still a hot topic of discussion because seeing the impact caused by interfaith marriages is very large. These impacts are child care, inheritance rights, child morals, and up to divorce. Often, interfaith marriages occur based on freedom of reasoning in religion. Thus, for people in an interfaith marriage, the perception of reason provides legal justification to strengthen the legality of interfaith marriages. Therefore, various efforts in interfaith marriages continue to be carried out in Indonesia. This research used the epistemology of Abed al-Jabiri, namely: Bayani, Burhani, and Irfani to emphasize reason as Idraku al-Sabab Wa al-Musabbab and reason as Bila Wasitah. This method is different from the epistemological methods of other figures such as Ibn Rushd and Ibn Khaldun. Thus, the researcher used al-Jabiri's epistemological trilogy as a method of thinking to see the freedom of reasoning in interfaith marriages. This research was qualitative research with heuristic methodical elements and used an epistemological approach. The heuristic method provides criticism of a certain paradigm so that the consequences of criticism become an alternative to a new paradigm. The results of this research were Abed al-Jabiri's criticism through an epistemological trilogy to provide limits on freedom of reasoning in interfaith marriages.